2019
DOI: 10.1194/jlr.p084590
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal lipid trends and adverse outcomes in patients with CKD: a 13-year observational cohort study

Abstract: Studies on the effects of longitudinal lipid trajectories on end-stage renal disease (ESRD) development and deaths among patients with chronic kidney disease (CKD) are limited. We conducted a registry-based prospective study using data from a 13-year multidisciplinary pre-ESRD care program. The final study population comprised 4,647 patients with CKD. Using group-based trajectory modeling, we dichotomized longitudinal trajectories of total cholesterol (T-CHO), triglyceride (TG), LDL cholesterol (LDL-C), and HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 56 publications
5
21
0
Order By: Relevance
“…Thompson et al also indicated that decreased eGFR was independently associated with lower concentrations of high-density lipoprotein and higher concentrations of triglycerides in an Australian population. In a longitudinal study, Tsai et al found that the level of total cholesterol, both at baseline and over the longitudinal course, was significantly associated with a higher risk of incident ESRD [43]. Similarly, in our current study, the serum concentration of total cholesterol was much higher in subjects with reduced eGFR than in subjects without reduced eGFR, and subjects with DKD…”
Section: Discussionsupporting
confidence: 81%
“…Thompson et al also indicated that decreased eGFR was independently associated with lower concentrations of high-density lipoprotein and higher concentrations of triglycerides in an Australian population. In a longitudinal study, Tsai et al found that the level of total cholesterol, both at baseline and over the longitudinal course, was significantly associated with a higher risk of incident ESRD [43]. Similarly, in our current study, the serum concentration of total cholesterol was much higher in subjects with reduced eGFR than in subjects without reduced eGFR, and subjects with DKD…”
Section: Discussionsupporting
confidence: 81%
“…Thompson et al also indicated that decreased eGFR was independently associated with lower concentrations of high-density lipoprotein and higher concentrations of triglycerides in an Australian population [47]. In a longitudinal study, Tsai et al found that the level of total cholesterol, both at baseline and over the longitudinal course, was significantly associated with a higher risk of incident ESRD [48]. Similarly, in our current study, the serum concentration of total cholesterol was much higher in subjects with reduced eGFR than in subjects without reduced eGFR, and subjects with DKD had the highest serum concentration of triglycerides.…”
Section: Discussionmentioning
confidence: 99%
“…Thompson et al also indicated that decreased eGFR was independently associated with lower concentrations of highdensity lipoprotein and higher concentrations of triglycerides in an Australian population [47]. In a longitudinal study, Tsai et al found that the level of total cholesterol, both at baseline and over the longitudinal course, was significantly associated with a higher risk of incident ESRD [48]. Similarly, in our current study, the serum concentration of total cholesterol was much higher in subjects with reduced eGFR than in subjects without reduced eGFR, and subjects with DKD had the highest serum [51].…”
Section: Discussionmentioning
confidence: 99%